Advances in research on chemical constituents and pharmacological effects of Paecilomyces hepiali - Akang Dan; Yujia Hu; Ruyan Chen; Xiangyang Lin; Yongqi Tian; Shaoyun Wang (Food Science and Human Wellness)
Paecilomyces hepiali is a fungus with edible and pharmaceutic value, isolated from Ophiocordyceps sinensis. Its main bioactive constituents contain alkaloids, cyclic dipeptides, steroids, organic acids, and polysaccharides. Due to the huge development potential of P. hepiali in the field of food and medicine, it has been developed into a variety of products that cater to the needs of the public. In this paper, the chemical constituents and their pharmacological effects of P. hepiali are reviewed, which can provide reference for the development and application of P. hepiali.